Behavior analysts in the war on poverty: A review of the use of financial incentives to promote education and employment. Issue 1 (11th January 2017) - Holtyn, August F.; Jarvis, Brantley P.; Silverman, Kenneth
Abstract : Poverty is a pervasive risk factor underlying poor health. Many interventions that have sought to reduce health disparities associated with poverty have focused on improving health‐related behaviors of low‐income adults. Poverty itself could be targeted to improve health, but this approach would require programs that can consistently move poor individuals out of poverty. Governments and other organizations in the United States have tested a diverse range of antipoverty programs, generally on a large scale and in conjunction with welfare reform initiatives. This paper reviews antipoverty programs that used financial incentives to promote education and employment among welfare recipients and other low‐income adults. The incentive‐based, antipoverty programs had small or no effects on the target behaviors; they were implemented on large scales from the outset, without systematic development and evaluation of their components; and they did not apply principles of operant conditioning that have been shown to determine the effectiveness of incentive or reinforcement interventions. By applying basic principles of operant conditioning, behavior analysts could help address poverty and improve health through development of effective antipoverty programs. This paper describes a potential framework for a behavior‐analytic antipoverty program, with the goal of illustrating that behavior analysts could be uniquely suited to make substantial contributions to the war on poverty.